KARAKTERISTIK BALOK LAMINASI KAYU AKASIA (Acacia Mangium) DAN MERANTI MERAH (Shorea leprosula) BERDASARKAN SUSUNAN LAMINA DAN BERAT LABUR PEREKAT STYROFOAM - Somadona , Sonia; Sribudiani, Evi; Elsa Valencia , Ditiya (Wahana Forestra: Jurnal Kehutanan, 2020)
The potential for wood raw materials in Indonesia is very abundant, but the increasing need for processed wood as a building material makes it difficult to obtain sawn timber in large sizes and with quality, due to the increasingly limiting logging in natural forests. High quality wood is hard to find in the market, so it is necessary to combine low quality and high quality wood by engineering the product with an adhesive, one of which is glued laminated timber. This study aims to see the characteristics of the glued laminated timber of Acacia mangium and Shorea leprosula based on the arrangement of lamina and the weight of adhesive Styrofoam. The blocks used in this study were 120 cm x 5 cm x 3 cm in size with the adhesive composition used was 60% Styrofoam and 40% gasoline with an glue spread of 200, 220 and 240 gr / m2. Observations made to produce data that is, the moisture content obtained layer ranged from 4.14 to 8.86%, a density of 0.38 to 0.51 g / cm3, MOE and MOR ranged from 24.78 to 86.71 kg / cm2.